Religious Institutions and Poverty Reduction: Evidence from Akwa Ibom State, Nigeria - Nsikak-Abasi A. Etim; Dorothy Thompson (Journal La Sociale, 2021)
In spite of the numerous poverty reduction policies and programs of successive administrations in Nigeria, the generality of the populace are still in a web of deprivation and hunger. It is apparent that government is unable to stem the tide of poverty and thus the need for surrogate stakeholders to lift the poor out of poverty. Therefore, an empirical study was conducted to estimate the factors influencing the willingness of religious institutions to undertake poverty reduction programs for it members and the constraints limiting their ability to initiate programs that will ameliorate the suffering of poor members in the congregation. A total of 60 churches were sampled through the multistage sampling procedure and information were elicited using questionnaire. Data were analyzed using probit model and Kendall’s coefficient of concordance. Result revealed that the most critical factors influencing the willingness of churches to undertake programs that will lift poor members of the congregation out of poverty were age and educational level of the church leaders, size of congregation, church income and age of the church. Result of Kendall’s coefficient of concordance indicated that there was 54 percent (moderate agreement) between the ranking of constraints associated with the willingness of churches to undertake programs that will lessen the pains of poverty among its members. Findings further showed that the top five most limiting constraints were lack of finance, lack of trained personnel, inadequate knowledge about the programs, unfavorable government policies and low membership strength.